LANGUAGE STYLE ANALYSIS USED BY AGNEZ MO AND RICH BRYAN'S INTERVIEW ON ASIA POP AND BUILD SERIES - Bertaria Sohnata Hutauruk; Partohap Sibhombing; Febrika Dwi Lestari; David Togi Hutapea (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
This research is focused on language style analysis used by Agnes Mo and Rich Bryans Interview on Asia Pop and Build Series. This research aims to classify the type of language style and the most dominant types used by Agnes Mo and Rich Bryans Interview on Asia Pop and Build Series. The data source of this research was YouTube AGNEZ MO full length interview on Asia Pop 40 which was aired on September, 29th 2016 and Indonesian Rapper Rich Brian Chats About His Single,